Kinerja Pembangunan Pertanian dalam Pelaksanaan Penggunaan Anggaran Tugas Pembantuan (TP) di Wilayah Propinsi Kalimantan Selatan - Winarso, Bambang (Jurnal Penelitian Pertanian Terapan, 2014)
South Kalimantan province is one of the potential locations for the development of food crops, especially rice. In line with the government especially the central government has tried in earnest to improve the performance of the agricultural development in the region is mainly to do with efforts to increase the harvested area, production, productivity of both rice crops, corn and soybeans. Aid funding through state funds and deconcentration assistance whose purpose is none other than the effort to reach. Fact shows that there are still any barriers, especially in terms of planning and implementation, especially regarding the budget allocation and the allocation of activities that still have not been synchronized. Keywords: employment dynamics, rural areas and dryland